Online curriculum development, review and resource contribution in partnership with the Hibulb Cultural Center and Natural History Preserve - Kupersmith, Alana (Kansas State University, 2024)
The paper describes the intent, process, and findings in implementing an online Indigenous People’s Social Studies curriculum that incorporates what local cultural institutions have to offer. Constructivism is the main theory embedded with Community of Inquiry, New Museum Theory, and Indigenous New Museum Theory. Subsequent pages describe planning as it relates to museum education programming and remote instruction as a partnership for schools and institutions. The content is specific to the institution but can be for all populations of students in the United States. I had the support of the Hibulb Cultural Center and Natural History Preserve to conduct research, create content, and volunteer virtually over an extended period.
Keywords: Indigenous Peoples; Indigenous New Museum Theory; New Museum Theory; Constructivism; Community of Inquiry; Museum Education Programming